Social Media as a Catalyst for Civic Engagement : A Case Study from Latin America - Ahmad Tauhid; Winur Windiyanti (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
This research examines the role of social media platforms in fostering civic engagement and political participation in Latin America. Through qualitative interviews and sentiment analysis, the study reveals how digital spaces amplify marginalized voices and mobilize communities for social change. However, it also highlights risks such as misinformation and polarization. Recommendations include leveraging social media for transparent communication and digital literacy programs.